ANALYSIS OF THE MAIN COMPONENTS OF THE INVESTMENT CLIMATE - Машошина, Тетяна; Батарчук, Олексій (SWorldJournal, 2025)
The article examines the main components of the investment climate. The dynamics of nominal and real GDP, GDP by final use, the inflation rate, the dynamics of external debt and gross external debt of Ukraine are analyzed. Their impact on the current sta